Global supply chain and port/terminal: integration and competitiveness - Song, Dongwook; Panayides, Photis (My University, 2008)
Much has been said of the importance of port and terminal integration in the supply chain. Authors have stressed the importance of agility to the port environment, which involves being proactive along supply chains, facilitation of intermodal integration, as well as organizational integration and partnership between ports and users. Despite the well articulated importance of the issues, little has been offered in terms of conceptualizations and empirical evidence of what really is meant by port/terminal integration in the supply chain, how such integration can be measured and quantified as well as the extent to which different ports/terminals in the world are integrated in the supply chain and competitive performance implications arising thereof. This paper aims to make a contribution in this respect by (i) reviewing the relevant literature on supply chain integration and port integration in the supply chain, (ii) conceptualizing measures for port/terminal integration in the supply chain, (iii) empirically testing the influence of port/terminal integration in the supply chain on port competitiveness and (iv) outlining the significance and value of the study for port operators, shipping lines, transport providers and for further research
Keywords: Harbors; Business logistics; Shipping; Transportation; Marine terminals